EDUKASI TATALAKSANA DIABETES MELITUS TIPE II DI KELURAHAN DUREN SAWIT JAKARTA TIMUR - Herty Nur Tanty; Fachdiana Fidia; Aries Meryta (Jurnal Pengabdian IKIFA, 2024)
Diabetes Mellitus (DM) is a chronic disease with a high incidence rate in Indonesia and is a serious problem for Indonesian people, especially in urban areas. It is estimated that by 2030 in Indonesia, DM sufferers will reach 21.3 million people. The aim of the Community Service (PkM) activity in Duren Sawit Village is to educate the public regarding the management of DM disease, especially type 2. The PkM activity was carried out on August 2, 2023, in the Duren Sawit Village Office Hall and was attended by 45 residents from several areas in Duren Sawit Village. The results of the PkM activities showed an increase in respondents' knowledge regarding the management of type 2 DM.